Scalable expansion of human pluripotent stem cells under suspension culture condition with human platelet lysate supplementation - Yuan, Haitao; Su, Hong; Wu, Chen; Ji, Yibing; Zhou, Lili; Wang, Lingna; Zhang, Haihong; Zhang, Xin; Tian, Xiaopeng; Zhu, Fangfang (Frontiers in Cell and Developmental Biology, 2023)
The large-scale production of human pluripotent stem cells (hPSCs), including both embryonic stem cells (hESCs) and induced pluripotent stem cells (hiPSCs), shows potential for advancing the translational realization of hPSC technology. Among multiple cell culture methods, suspension culture, also known as three-dimensional (3D) culture, stands out as a promising method to fulfill the large-scale production requirements. Under this 3D culture condition, cell expansion and the preservation of pluripotency and identity during long-term culture heavily relies on the culture medium. However, the xenogeneic supplements in culture medium remains an obstacle for the translation of cell and gene therapy applications from bench to bedside. Here, we tested human platelet lysate (hPL), a xeno-free and serum-free biological material, as a supplement in the 3D culture of hPSCs. We observed reduced intercellular variability and enhanced proliferation in both hESC and hiPSC lines. These cells, after extended culture in the hPL-supplemented system, maintained pluripotency marker expression, the capacity to differentiate into cells of all three germ layers, and normal karyotype, confirming the practicability and safety of hPL supplementation. Furthermore, through RNA-sequencing analysis, we found an upregulation of genes associated with This is a provisional file, not the final typeset article cell cycle regulations in hPL-treated cells, consistent with the improved cellular division efficiency. Taken together, our findings underscore the potential of hPL as a xeno-free and serum-free supplement for the large-scale production of hPSCs, which holds promise for advancing clinical applications of these cells.